Analyst Report Readability1. (28th July 2014) - De Franco, Gus; Hope, Ole‐Kristian; Vyas, Dushyantkumar; Zhou, Yibin
<x xml:space="preserve">Abstract</x> Using an extensive database of 356, 463 sell‐side equity analysts' reports from 2002 to 2009, this study is one of the first to analyze the readability of analysts' reports. We first examine the determinants of variations in analyst report readability. Using several proxies for ability, we show that reports are more readable when issued by analysts with higher ability. Second, we test the relation between analysts' report readability and stock trading volume reactions. We find that trading volume reactions increase with the readability of analysts' text, consistent with theoretical models that predict that more precise information (and hence more informative signals) results in investors' initiating trades. These results support the view that the readability of analysts' reports is important to analysts and capital market participants.